SUSTAINABLE MENTORING IN THE USE OF ONLINE LEARNING PLATFORMS TO ENHANCE THE EFFECTIVENESS OF CHRISTIAN RELIGIOUS EDUCATION TEACHING IN RURAL SCHOOLS [A SYSTEMATIC LITERATURE REVIEW] - Esterani; Resti; Daniel Nianda; Theodorus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This article presents a systematic literature review on continuous mentoring in using online platforms to enhance the effectiveness of Christian Religious Education (CRE) teaching in rural schools. Based on an analysis of 17 empirical articles (2020-2024), this study identifies multidimensional challenges faced by teachers, including limited infrastructure, low digital pedagogy competence, and psychological barriers such as technostress. The synthesis reveals that effective mentoring models are sustainable and contextual, combining instructional coaching for individual support and virtual communities of practice (VCoP) for peer collaboration. This approach significantly enhances complex dimensions of teachers' TPACK particularly Technological Pedagogical Knowledge (TPK) and Technological Content Knowledge (TCK) enabling them to design more interactive, reflective, and contextual online CRE learning. Key success factors include contextualizing materials for low-bandwidth conditions, building trust-based mentor-teacher relationships, and active support from school leadership. The findings provide an evidence-based foundation for policymakers and practitioners to design targeted mentoring programs that improve the quality of online CRE learning in rural areas.